2010
DOI: 10.1103/physreva.81.013828
|View full text |Cite
|
Sign up to set email alerts
|

Spatial two-photon coherence of the entangled field produced by down-conversion using a partially spatially coherent pump beam

Abstract: We study the spatial coherence properties of the entangled two-photon field produced by parametric downconversion (PDC) when the pump field is, spatially, a partially coherent beam. By explicitly treating the case of a pump beam of the Gaussian Schell-model type, we show that in PDC the spatial coherence properties of the pump field get entirely transferred to the spatial coherence properties of the down-converted two-photon field. As one important consequence of this study, we find that, for two-qubit states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…We note that in situations in whichγ d (∆τ ′ ) ≈ 1 and κ 1 = κ 2 , the maximum achievable concurrence for a pulsed field can be unity in principle and for a continuous-wave field it can be unity as long as ∆τ is much smaller than the coherence time of the pump field. The above result is the temporal analog of the results obtained in the polarization [31] and spatial [19] degrees of freedom. However, unlike in the spatial degree of freedom, which does not involve any space-averaged detection scheme, the results derived in this article show that even for the time-averaged detection schemes, the temporal correlation properties of the pump do directly decide the upper limit on entanglement that a time-energy entangled two-qubit state can achieve.…”
Section: Rsupporting
confidence: 76%
See 2 more Smart Citations
“…We note that in situations in whichγ d (∆τ ′ ) ≈ 1 and κ 1 = κ 2 , the maximum achievable concurrence for a pulsed field can be unity in principle and for a continuous-wave field it can be unity as long as ∆τ is much smaller than the coherence time of the pump field. The above result is the temporal analog of the results obtained in the polarization [31] and spatial [19] degrees of freedom. However, unlike in the spatial degree of freedom, which does not involve any space-averaged detection scheme, the results derived in this article show that even for the time-averaged detection schemes, the temporal correlation properties of the pump do directly decide the upper limit on entanglement that a time-energy entangled two-qubit state can achieve.…”
Section: Rsupporting
confidence: 76%
“…In the polarization degree of freedom it was shown [31] that the degree of polarization P of the pump photon puts an upper bound of (1 + P )/2 on the concurrence of the generated twoqubit state. In the spatial degree of freedom, effects of pump spatial coherence on the entanglement of the generated spatial two-qubit state have been worked out for two-qubit state that have only two non-zero diagonal elements, and for such states it has been shown that the concurrence is bounded by the degree of spatial coherence of the pump field [19]. However, to the best of our knowledge, no such relation has so far been derived for the time-energy entangled two-qubit states.…”
Section: The Special Case Of a Gaussian Schell-model Pump Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Fundamentally, our analysis demonstrates that the lack of momentum correlation does not imply an violation of the conservation of momenta; it shows that the coherence of the pump, i.e. its 'quantumness', is crucial for the generation of entangled photons.A first theoretical analysis [17,18] of the pairgeneration process shows that the angular profile of the pump and its coherence is transferred to the downconverted light. Thus, it determines the uncertainty of the anti-correlation and also effects the generation of entanglement.…”
mentioning
confidence: 99%
“…In recent years, transfer of the coherence properties of the pump photon to the signal and idler photons has been studied in various different contexts [40,45,46]. In this section, we investigate this transfer in terms of the intrinsic degree of coherence.…”
Section: Transfer Of Intrinsic Degree Of Coherence In Pdcmentioning
confidence: 99%